An Accuracy Assessment of Forensic Computerized Facial Reconstruction Employing Cone-Beam Computed Tomography from Live Subjects - Lee, Won-Joon; Wilkinson, Caroline M.; Hwang, Hyeon-Shik (Journal of forensic sciences, 2012)
:  The utilization of 3D computerized systems has allowed more effective procedures for forensic facial reconstruction. Three 3D computerized facial reconstructions were produced using skull models from live adult Korean subjects to assess facial morphology prediction accuracy. The 3D skeletal and facial data were recorded from the subjects in an upright position using a cone‐beam CT scanner. Shell‐to‐shell deviation maps were created using 3D surface comparison software, and the deviation errors between the reconstructed and target faces were measured. Results showed that 54%, 65%, and 77% of the three facial reconstruction surfaces had <2.5 mm of error when compared to the relevant target face. The average error for each reconstruction was −0.46 mm (SD = 2.81) for A, −0.31 mm (SD = 2.40) for B, and −0.49 mm (SD = 2.16) for C. The facial features of the reconstructions demonstrated good levels of accuracy compared to the target faces.